The community structure of macroscopic basidiomycetes (Fungi) in Brazilian mangroves influenced by temporal and spatial variations - Santos Nogueira-Melo, Georgea (Universidad de Costa Rica, 2014)
Mangroves are transitional ecosystems between terrestrial and marine environments, and are distinguished by a high abundance of animals, plants, and fungi. Although macrofungi occur in different types of habitat, including mangroves, little is known about their community structure and dynamic. Therefore the aim of this study was to analyze the diversity of macrofungi in a number of Brazilian mangroves, and the relationship between such diversity, precipitation and area of collection. A total of 32 field trips were undertaken from 2009 to 2010, and macrofungi were studied in four 250×40m transects: Timbó and Santa Cruz Channel on the Northern coast, and Maracaípe and Ariquindá on the Southern coast. All basidiomata found along the transects were placed in paper bags, air-dried and identified using existing literature. It was found that Northern areas predominantly featured Avicennia schaueriana mangroves, while Rhizophora mangle dominated in Southern transects. A total of 275 specimens were collected, and 33 species, 28 genera, 14 families and six orders were represented. Overall abundance and species richness did not vary significantly among areas, but varied according to time, being higher during the rainy season. Subtle differences in composition were observed over time and between areas, probably due to variations in plant species occurrence. Further studies with collections during months of greater precipitation in transects dominated by different mangrove species of the same ecosystem are suggested to assess the overall diversity of mycobiota in these ecosystems.